Study of Patient Satisfaction on the Quality of Inpatient Service of RSUD Ben Mboi Ruteng - Yoseph Kenjam; Masrida Sinaga; Akulina Mayangtika (Universitas Nusa Cendana, 2023)
RSUD Ben Mboi Ruteng is one of the health service facilities in Manggarai. This hospital has not been able to meet the needs of patients because it is still experiencing a shortage of beds, health workers, and medicines; indicators have yet to reach the target, programs have not been running, and services have not been maximized. The inability of the hospital to provide services according to patient needs impacts patient dissatisfaction with the quality of hospital inpatient services. This study aimed to describe the level of patient satisfaction with five dimensions of health service quality: reliability, responsiveness, assurance, empathy, and tangible in the Flamboyant Room of RSUD Ben Mboi Ruteng. This research is quantitative descriptive research with a public opinion survey research design. The data was collected using observation, literature, and documentation by measuring 80 respondents. Samples were obtained using the purposive sampling method and data analysis by univariate. The results showed that most of the respondents were satisfied with reliability (78,8%), assurance (86,2%), empathy (73,8%), and tangible (87,5%), while the responsiveness mostly felt dissatisfied (61,25%). The hospital must follow up on health services, especially in responsiveness. The house must improve services that have not been maximized, such as allowing patients to ask questions and explain about the disease by providing exceptional training on ethics or doctor's behavior in providing health services so that patients are satisfied with the services offered.